Damaging Discourse in Online News Trends Over Ecological Literacy - Saifulloh, Ahmad Iklil; Retnaningdyah, Pratiwi; Mustopa, Ali; Suhartono (ELITE JOURNAL, 2023)
ABSTRACT The major objective of this research is to have a substantial impact on the damaging discourse of trends in online news of Eco literacy, beginning with a discussion of its locus of Ecology, Eco-literacy, and Eco linguistics in Indonesia in the wake and post-pandemic age. Then the study presents some of the antecedents of the worst condition of literacy around us in Indonesian Nature, continuing into the emergence of uncontrolled conditions of news that hypnotizes our way of living. Further, it presents a comprehensive and historical conspectus of Eco Literacy as it exists today, including some of the fundamental ideas by Arran Stibbe, David Orr, Kathy Ann Mills, Khan, Greg Gerard, and the Social Practice of Bang & Door. By applying phenomenological research, NVivo 12 Plus, this study applies a Qualitative Data Analysis (QDA) model to find out how language in online news might modify the consumptive paradigm and is not under environmental ethics in social society through online media. Finally, the result of the research indicates three coding in form of nodes in NVivo that covers Ideological Background; 23 references in 9 news, Sociological Background in Social Millau; 6 references in 5 news, and Biological Background; 5 references in 5 news. And all those findings lead to on big finding, the struggle for environmental destruction. Keywords: Eco Literacy; eco linguistics, digital literacy, EFL